Impacts of climate change on rivers and biodiversity in a water-scarce semi-arid region of the Western Cape, South Africa - Tanner, Jane; Mantel, Sukhmani; Paxton, Bruce; Slaughter, Andrew; Hughes, Denis (Frontiers in Water, 2022)
The Ecological Reserve (environmental flows) as defined under the South African National Water Act 36 of 1998 was designed to equitably manage water for river sustainability while maximising economic and social welfare. We investigated the climate change impacts on the Ecological Reserve targets for a seasonal river in an agricultural catchment in the Western Cape region using the Habitat Flow Stressor Response method (which integrates hydrology, hydraulics, water quality and ecological data) under projected climate scenarios (2041-2070). Current Ecological Reserve model outcomes for 3 sites on the Doring River were compared with the future hydrology using Global Circulation Models associated with four Representative Concentration Pathways (RCP 2.6 to 8.5). Climate predictions reflected reduced future flows, but the uncertainty band of predicted future flows overlapped with present day flows. Flood flashiness following heavy rains and the increased length of dry periods that are predicted would both contribute to increased erosion and geomorphological degradation, and further compromise biodiversity including the endangered fish populations and threaten both freshwater and estuarine ecosystems downstream. Salinity variation is predicted to increase in future leading to increased seasonal salinity stress and reduced use of abstracted water. We interrogate various options for mitigating the impacts including augmenting dry season flows, developing on-farm, catchment-scale and strategic water resources management, and removing alien vegetation.